An examination of ice hockey players' imagery use and movement imagery ability - Hallman, T. A. D.; Munroe-Chandler, K. J. (Journal of Imagery Research in Sport and Physical Activity, 2009)
Imagery is an effective performance enhancing technique for athletes (Driskell, Copper, & Moran, 1994), and therefore has been the topic of extensive investigation in the sport psychology domain. To date, the few studies that have examined imagery across position of play have neglected to examine goaltenders as a distinct position from defense. As such, comparisons can only be made between forwards and defense. The purpose of the present study was to examine influence of playing position on imagery use and movement imagery ability in elite male ice hockey players. Participants included 258 competitive male ice hockey players (n = 122 forwards, n = 68 defense, n = 68 goaltenders), between the ages of 16 and 29 years (19.12 ±1.96). Two separate MANOVAs revealed significant overall effects for both imagery frequency and imagery ability across playing position. Univariate follow-up ANOVAs found that goaltenders use significantly more MG-M and CS imagery than forwards and defense. Furthermore, it was found that goaltenders indicated clearer and more vivid images from an internal and external perspective than forwards. Findings from the present study provide sport psychologists with research that can guide the development of more individually tailored imagery interventions for ice hockey athletes.